Evaluating the effects of a symmetric instability parameterization scheme in the Xisha-Zhongsha waters, South China Sea in winter - Jiang, Yifei; Dong, Jihai; Zhang, Xiaojiang; Zhang, Wenjing; Wang, Huizan; Zhang, Weimin (Frontiers in Marine Science, 2022)
As one of the important submesoscale instabilities, symmetric instability (SI) widely exists in the ocean surface mixed layer (SML), which enhances the vertical material transport in the SML and also the exchanges between the SML and the ocean interior. Due to the small spatial scales of SI, O (10 m–1 km), which are not resolved by most current ocean models, the application of SI parameterization is an alternative choice in the coming decades to include the SI effects in ocean models and improve the model performance. In this study, we evaluate the impacts of SI in a realistic configuration with the SI parameterization scheme applied in the Xisha-Zhongsha waters, South China Sea in winter by using the Coastal and Regional Ocean Community Model (CROCO) version of the Regional Ocean Modeling System. Compared to the SI-lacking case, the SI energy source, the geostrophic shear production, is increased and elimination of anticyclonic potential vorticity is revealed in the SI-parameterized case. According to the energy analysis, multi-scale interactions are also influenced by the SI. The effective wind energy input is reduced, and the potential energy release in the SML is suppressed. Moreover, the SI scheme makes the SML depth shallower and closer to the reanalysis one. This work demonstrates a good performance of the SI scheme applied in regional models in representing SI effects.